Socio-cultural Inspired Metaheuristics - Kulkarni, Anand J.; Singh, Pramod Kumar; Satapathy, Suresh Chandra; Husseinzadeh Kashan, Ali; Tai, Kang (Studies in Computational Intelligence, 2019)
This book presents the latest insights and developments in the field of socio-cultural inspired algorithms. Akin to evolutionary and swarm-based optimization algorithms, socio-cultural algorithms belong to the category of metaheuristics (problem-independent computational methods) and are inspired by natural and social tendencies observed in humans by which they learn from one another through social interactions. This book is an interesting read for engineers, scientists, and students studying/working in the optimization, evolutionary computation, artificial intelligence (AI) and computational intelligence fields.